Cutaneous Manifestations in End-Stage Renal Disease (ESRD) - Rahmatika, Amira Suryani; Setyaningrum, Trisniartami; Sawitri, Sawitri; Ervianti, Evy; Damayanti, Damayanti (Universitas Muhammadiyah Surabaya, 2024)
Skin can reflect systemic conditions due to abnormalities in internal organs, including kidney disorders. Cutaneous manifestations are common in patients with end-stage renal disease (ESRD). It can be severe and negatively impact a patient's quality of life. Clinicians can effectively manage ESRD by closely examining the patient's skin and nails, improving the patient's quality of life, and reducing mortality and morbidity. Clinicians can be more aware of ESRD by examining the patient's skin and nails closely so proper management can be performed and the patient's quality of life can be improved. This review aims to increase understanding of common cutaneous manifestations in ESRD for early recognition and better management. Cutaneous manifestations in ESRD are divided into specific and nonspecific manifestations. Specific manifestations include acquired perforating dermatosis (APD), bullous disease (porphyria cutanea tarda and pseudoporphyria), metastatic calcification (calcinosis cutis and calcific uremic arteriolopathy), and nephrogenic systemic fibrosis. Nonspecific manifestations include pruritus, xerosis, skin pigmentation changes, nail disorders, purpura, hair disorders, oral mucosal changes, skin infections, and other skin manifestations. These manifestations range from benign and asymptomatic to serious conditions that negatively impact life quality. In conclusion, Early detection and treatment of cutaneous manifestations in patients with ESRD are crucial for reducing morbidity and mortality and also improving patients' quality of life.